2020
DOI: 10.1186/s12893-020-00873-x
|View full text |Cite
|
Sign up to set email alerts
|

The segment IV approach: a useful method for achieving the critical view of safety during laparoscopic cholecystectomy in patients with anomalous bile duct

Abstract: Background The critical view of safety (CVS) method can be achieved by avoiding vasculo-biliary injury resulting from misidentification during laparoscopic cholecystectomy (LC). Although achieving the CVS has become popular worldwide, there is no established standardized technique to achieve the CVS in patients with an anomalous bile duct (ABD). We recently reported our original approach for securing the CVS using a new landmark, the diagonal line of the segment IV of the liver (D-line). The D-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…[15,36,37,43] Although there are models predicting difficulty, they are complex and not practical. [7][8][9][10]24,25,34,44,[44][45][46][47][48] . To predict the use of a bailout procedure in a more practical way, we estimated the area under the ROC curve of the time (minutes) spent trying to dissect the CD and found that it predicts the use of bailout techniques, as well as being a good predictor of conversion (see Graphs 1 and 2).…”
Section: Discussionmentioning
confidence: 99%
“…[15,36,37,43] Although there are models predicting difficulty, they are complex and not practical. [7][8][9][10]24,25,34,44,[44][45][46][47][48] . To predict the use of a bailout procedure in a more practical way, we estimated the area under the ROC curve of the time (minutes) spent trying to dissect the CD and found that it predicts the use of bailout techniques, as well as being a good predictor of conversion (see Graphs 1 and 2).…”
Section: Discussionmentioning
confidence: 99%
“…So, it is absolutely safe to dissect in this area regardless of the presence of any vascular or biliary anomalies, or severe inflammation in the Calot's triangle [ 1 ]. Fujioka et al [ 7 ] used the D-line approach for LC in patients with bile duct anomalies and found that it was safe and very effective in avoiding BDIs. The D-line served as a landmark to help surgeons dissect Calot's triangle to the right side and away from the hilar plate, which is known to be the convergence point for all biliary ducts, including the anomalous bile duct [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the D-line approach has been used but with some modifications to the previously described technique [ 1 , 7 ]. The falciform ligament was not tied or retracted extracorporeally because the cephalad retraction of the GB was enough to expose the inferior surface of segment IV.…”
Section: Methodsmentioning
confidence: 99%
“…Fujioka et al . [ 29 ] used the “segment 4” approach for difficult laparoscopic cholecystectomy, which was a line connecting the right dorsal and left ventral corners of segment 4. However, the line of “segment 4” may be variable due to the different shapes of the quadrate lobe [ 30 ].…”
Section: Discussionmentioning
confidence: 99%